Research on Determination Method and Influencing Factors of Porosity of Wheat Pile - LI Qian-qian; CHEN Xin; BI Wen-ya; JIANG Jun-yi; SHI Tian-yu (Liang you shipin ke-ji, 2021)
TSZ-6A strain-controlled triaxial apparatus was used to determine bulk density of wheat under different pressures and initial pressure porosity was tested by self-made porosity mete， the porosity values of samples under different varieties， water content and pressure were calculated according to the relationship between bulk density and porosity. The results showed that the porosity of wheat decreased with the increase of pressurewhich satisfied the power function relationship; The porosity of wheat increased with the increase of water content， which satisfied the quadratic function relationship; In a certain size range， varieties had no obvious effect on porosity.